2015
DOI: 10.21776/ub.jpacr.2015.004.03.220
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Implantation Activity of Kepel (Stelechocarpus burahol) Pulp Ethanol Extract in Female Mice

Abstract: Kepel (Stelechocarpus burahol) has been used as a contraceptive remedy in Indonesian traditional Javanese royal family. It fruit contains a toxic substances to fetus. However, few studies have been conducted on the toxic effect of kepel fruit. This paper is disclosed the effects of kepel's fruit extract on the percentage of fetus death, ovaries weight, and endometrial thickness in female mice. This study applied a post-test control group design. A 28 female of mice were divided into 4 groups. Group I (control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…From the results of the study, it can be seen that the inhibition of the growth of bacterias is thought to be caused by antibacterial compounds contained in the methanol extract of kepel leaves. Kepel's leaf it known contains terpenoids and flavonoids as the secondary metabolites [6]. Leaves extracts of kepel contains flavonoids include auron, flavanones and flavanols that can be used for antibacterial agent [7].…”
Section: Antimicrobial Test Results For Tablet Preparationsmentioning
confidence: 99%
“…From the results of the study, it can be seen that the inhibition of the growth of bacterias is thought to be caused by antibacterial compounds contained in the methanol extract of kepel leaves. Kepel's leaf it known contains terpenoids and flavonoids as the secondary metabolites [6]. Leaves extracts of kepel contains flavonoids include auron, flavanones and flavanols that can be used for antibacterial agent [7].…”
Section: Antimicrobial Test Results For Tablet Preparationsmentioning
confidence: 99%
“…The formula containing fruit pulp is known as "awetayu" (remain beautiful). 1 Some biological activities of kepel have been reported namely anti-hyperuricemic and xanthine oxidase inhibitor, 2 anti-inplantation, 3 anticancer, 4 antiseptic, 5 anti-inflammation, 6 and antioxidant activities. 7,8 It was reported that ethanol extract of kepel leaves did not induce the toxic effect on male and female Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that fuit pulp had potential as a natural deodorant since it had adsorbent function and probiotic activation by increase the growth of Bifidobacteria so the population of odorant producing bacteria will be reduced [5]. The fruit pulp of kepel also reported contains high antioxidant [6], and contains alkaloids, flavonoids, polyphenols, triterpenoids, saponins and quinones as well have the effect of anti-implantation [7]. Kepel's leaf contains terpenoids and flavonoids [7].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit pulp of kepel also reported contains high antioxidant [6], and contains alkaloids, flavonoids, polyphenols, triterpenoids, saponins and quinones as well have the effect of anti-implantation [7]. Kepel's leaf contains terpenoids and flavonoids [7]. Leaves extracts of kepel contains flavonoids include auron, flavanones and flavanols that can be used for antibacterial [9].…”
Section: Introductionmentioning
confidence: 99%